2020
DOI: 10.1002/bio.3916
|View full text |Cite
|
Sign up to set email alerts
|

One‐step synthesis of cationic gold nanoclusters with high catalytic activity on luminol chemiluminescence reaction

Abstract: The present study reports a one‐step synthesis method for the preparation of cationic gold nanoclusters (Au NCs). Polyethyleneimine (PEI), a positively charged hyperbranched polyamine, was selected as the capping reagent. Glutathione showed a synergistic effect on the formation of the small size of cationic Au NCs. The prepared cationic Au NCs have a size less than 2 nm and carry a positive charge in solution with pH less than 11. The cationic PEI–Au NCs‐triggered luminol chemiluminescence (CL) reactions showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Luminol-based chemiluminescence (CL) system is well-known as one of the powerful methodologies for reactive oxygen species (ROS) because of its ability to produce strong CL emission. However, as a classical CL system, the H 2 O 2 –luminol system is usually subject to the self-decomposition of H 2 O 2 , which affects its application to a certain extent, while ROS are active in chemical reactions and could trigger luminol to produce intense CL emission. Therefore, it is urgent to find a stable and controlled reactant in CL reaction. Hence, researchers turned their attention to the efficient generation process of ROS, especially nanomaterials. For example, graphene oxide or carbon nitride treated by H 2 O 2 could form stable carbon radicals and ROS on the π bond of the lamellar structure and produce strong CL emission with luminol. , …”
Section: Introductionmentioning
confidence: 99%
“…Luminol-based chemiluminescence (CL) system is well-known as one of the powerful methodologies for reactive oxygen species (ROS) because of its ability to produce strong CL emission. However, as a classical CL system, the H 2 O 2 –luminol system is usually subject to the self-decomposition of H 2 O 2 , which affects its application to a certain extent, while ROS are active in chemical reactions and could trigger luminol to produce intense CL emission. Therefore, it is urgent to find a stable and controlled reactant in CL reaction. Hence, researchers turned their attention to the efficient generation process of ROS, especially nanomaterials. For example, graphene oxide or carbon nitride treated by H 2 O 2 could form stable carbon radicals and ROS on the π bond of the lamellar structure and produce strong CL emission with luminol. , …”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that AuNPs act as a catalyst to decompose hydrogen peroxide to form • OH, which can react with luminol to enhance CL. 29,30 Based on this catalytic reaction, Cui and co-workers proposed a series of luminol-type CL reagent-functionalized AuNPs. These functionalized AuNPs with excellent CL performance had been successfully applied in immunoassays and DNA assays.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chemiluminescence (CL), deriving from the exciton in chemical reactions, has been one of the most powerful means for the fabrication of a simple and sensitive sensing platform due to its rapidity, simple operation, high signal contrast, and wide range of analytes. In the evolution of CL techniques, gold nanoparticles have been demonstrated to serve as nanoenzymes and emitters for a dramatic increase of CL performance. The AuNP-catalytic reaction also shows talent in improving analytic performance via tailoring the molecule. It is well-known that AuNPs act as a catalyst to decompose hydrogen peroxide to form • OH, which can react with luminol to enhance CL. , Based on this catalytic reaction, Cui and co-workers proposed a series of luminol-type CL reagent-functionalized AuNPs. These functionalized AuNPs with excellent CL performance had been successfully applied in immunoassays and DNA assays. Na’s group showed that luminol could generate emission only from radical-mediated spin transfer on the catalyst-like gold nanoclusters (AuNCs) and subsequently fabricated a sensor array containing five protein-protected AuNCs for discriminating proteins .…”
Section: Introductionmentioning
confidence: 99%
“…[ 19–21 ] Luminol and its derivatives, as one of the classical luminescent reagents used in CL analysis, are widely used in CL analysis and detection because of relatively good stability, relatively high luminescence quantum yield, simple synthesis method, and other characteristics. [ 22 ] Cui's group [ 23 ] successfully achieved direct reduction of HAuCl 4 with luminol and obtained gold nanoparticles coated with multiple luminol molecules and their oxidation products, which not only had outstanding CL properties, but also showed satisfactory catalytic performance and biocompatibility. The ability to bind sulfhydryl‐functionalized stem–loop DNA molecules makes luminol‐functionalized gold nanoparticles (LumAuNPs) one of the choices for CL probe materials.…”
Section: Introductionmentioning
confidence: 99%